Galaxy cluster mass reconstruction project - I. Methods and first results on galaxy-based techniques - Old, Lyndsay; Skibba, R.A.; Pearce, Frazer R.; Croton, D.; Muldrew, Stuart I.; Muñoz-Cuartas, J.C.; Gifford, D.; Gray, M; der Linden, A. von; Mamon, G.A.; Merrifield, Michael R.; Müller, V.; et al. (Oxford University Press, 2014)
This paper is the first in a series in which we perform an extensive comparison of various galaxy-based cluster mass estimation techniques that utilize the positions, velocities and colours of galaxies. Our primary aim is to test the performance of these cluster mass estimation techniques on a diverse set of models that will increase in complexity. We begin by providing participating methods with data from a simple model that delivers idealized clusters, enabling us to quantify the underlying scatter intrinsic to these mass estimation techniques. The mock catalogue is based on a Halo Occupation Distribution (HOD) model that assumes spherical Navarro, Frenk and White (NFW) haloes truncated at R₂₀₀, with no substructure nor colour segregation, and with isotropic, isothermal Maxwellian velocities. We find that, above 1014Mʘ, recovered cluster masses are correlated with the true underlying cluster mass with an intrinsic scatter of typically a factor of 2. Below 1014Mʘ, the scatter rises as the number of member galaxies drops and rapidly approaches an order of magnitude. We find that richness-based methods deliver the lowest scatter, but it is not clear whether such accuracy may simply be the result of using an over-simplistic model to populate the galaxies in their haloes. Even when given the true cluster membership, large scatter is observed for the majority non-richness-based approaches, suggesting that mass reconstruction with a low number of dynamical tracers is inherently problematic.